Do women's team members combined career durations in the Olympic Games and world championships influence team outcomes? A historical examination - 1936 to 2016 - Sands, W.; Donti, O. (Science of Gymnastics Journal, 2018)
U.S.A.`s Women`s Gymnastics team has performed exceptionally at the Olympic Games and World Championships in recent years. One of the aspects of performance thought to be important in team events is the prior experience of the athletes. Prior experience can be measured by an athlete`s total number of world level competitions and career durations prior to a given competition. Olympic and World Championship team rosters and team ranks were examined from 1936 to 2016. The number of competitions per athlete and ranks of the teams were tallied and analyzed over the entire period. There were 193 individual athletes and 43 competitions. Athlete career durations were determined by calculation of years between competitions in which the athlete participated. Time-series regression analyses showed no relation between career durations and time while there was a statistically significant trend of team rank reduction (better team finishes) over time. After dividing the study period into two-time segments, there were no statistical differences between early and late periods in career durations, while there were statistical differences in team ranks over the same durations. Olympic Games and World Championships were separated and again there was no statistical difference between the two competition levels on career durations nor did the ranks of the two periods show statistical differences. There did not appear to be a relationship between career durations and team performance ranks.